Services and Their Role in the National Economy: Notions Transformation - Latkin, Alexander P.; Krochmal, Larisa; Kovshun, Juliya (International Review of Management and Marketing, 2016)
Services are involved in consumer, intermediary and public markets and contain processes of varying complexity, including state transformation of physical objects, people or codified data. So there is quite a wide range of studies that have expressed doubts about the accuracy of the properties traditionally attributed to the service. An open dialogue between members of the scientific community, as well as the dialogue of researchers with entrepreneurs becomes the basis for the development of a new paradigm of service. According to the opinion of many authors the service cannot be regarded as a general category, it is time to consider its characteristics which are justified by the practice and differ from the purely theoretical ideas. At the heart of these changes there is an impact of innovations on services development, which forces companies to change the organizational rules, regulations and interaction process within the company and to move to a new “lifestyle”, focusing on consumer preferences. Keywords: service, innovation, consumer preferences, companies, development JEL Classifications: A10, M10, D11